Diels–Alder Reactions of 1,2-Dihydropyridines: An Efficient Tool for the Synthesis of Isoquinuclidines - Silva, Eduarda M. P.; Rocha, Djenisa H. A.; Silva, Artur M. S. (Synthesis, 2018)
The Diels–Alder reaction of 1,2-dihydropyridines with different dienophiles is a well-established and straightforward method for the synthesis of isoquinuclidines. Nevertheless, the enantioselective preparation of isoquinuclidines using organocatalysts or organometallic catalysts is rather unexplored. This succinct review offers readers an overall perspective of the most important recent developments and concepts related to this topic.1 Introduction2 Asymmetric Diels–Alder Reaction of 1,2-Dihydropyridines2.1 Transition-Metal-Catalyzed Reactions2.2 Organocatalyzed Reactions3 Diels–Alder Reaction of 1,2-Dihydropyridines in the Synthesis of Biologically Valuable Compounds4 Conclusion
Keywords: organocatalysis; organometallic catalysis; asymmetric transformations; enantioselective reactions; Lewis acids; alkaloids; ibogaine; Tamiflu